The Unified Supplementary Damping Method Based on Voltage-Soured Converter High-Voltage Direct Current Transmission Through Robust Control - Jinlei, Zhu; Yao, Zhang; Feixiang, Wu; Jiachang, Yi; Jiaqi, Wu (Frontiers in Energy Research, 2022)
The voltage sourced converter based high-voltage direct-current (VSC-HVDC) system can damp the inter-area low frequency oscillation effectively. To enhance the ability of the VSC-HVDC supplementary control, this paper proposes a unified low frequency oscillation controller design through robustness theory. The unified control strategy uses both the active power control and reactive power control loop of the VSC to expand the supplementary control dimensions. To design the controller, the total least square estimation of signal parameters via rotational invariance techniques (TLS-ESPRIT) identification method is used to obtain the system small signal model and the oscillation characteristic. Based on the model identified out, the linear matrix inequality method based robust control theory is applied for controller design. And the robust controllers for active power control and reactive power control loop are both designed to improve the control effect. Finally, the simulation results shows that the controller can reach better control effect and the robustness can also be guaranteed.